Hubungan Kekerabatan Bahasa Jawa Dan Bahasa Melayu (Kajian Linguistik Historis Komparatif) - Sunu Setiawan Utama; Andhika Wirya Nuswantoro; Andrian Febrianto; Slamet Mulyono (Jurnal Pendidikan, Bahasa dan Budaya, 2023)
Language as a means of human communication has become one of the interesting studies from time to time considering that language is dynamic. The science that studies language is linguistics, in which between branches of linguistics there is comparative historical linguistics. This study aims to describe how comparative linguistic studies are between Javanese regional languages and Malay regional languages. This research uses descriptive qualitative and quantitative methods. Qualitatively it functions to collect data and analyze it both orally and in writing, while quantitatively to get comparisons and the number of percentages between language kinships obtained by using lexicostatistics techniques. The data source for this research is a Pontianak Malay language text entitled Bawang Merah and Bawang Puteh . The steps taken to determine language kinship are: (1) determine the basic vocabulary of Bawang Merah and Bawang Puteh folklore, (2) determine the pairs of the two languages, (3) determine the time of separation and age of language kinship. Based on the results of the analysis, Javanese and Malay were the only languages between 2325 – 1845 years ago. Javanese and Malay languages separated into a proto language between 302 - 178 AD (calculated by 2023).